Allusions To Iraqi Wars In Suzanne Collins' The Hunger Games 2008 (Journal of the College of Basic Education, 2022)
Suzanne Collins in all her interviews considered Iraqi war a major source and inspiration for her The Hunger Games trilogy. Although many researches and studies thoroughly studied all possible sources and inspiration for the trilogy, no research studied Iraq as an inspiration. The aim of the research was to detect and analyze all allusions to Iraqi wars in the Hunger Games 2008. The novel consists of three parts; part one portrays a postapocalyptic country called Panem struck with poverty, disease and hunger. Panem is a striking allusion to Iraq after the apocalyptic Iran – Iraq war, Gulf War 1991 and Embargo 1991 – 2003. The second part describes The Hunger Games as the Gulf War 1991 incarnated. The third part of the novel depicts the victors of the hunger games as rebels and how the dictatorship of President Snow eliminated his rebels which is a clear allusion to the former Iraqi President Saddam Hussein and his genocides against the Iraqi Uprisings1991. The researcher concluded that The Hunger Games carries so many allusions to the Iraqi wars that it can be considered a historical account of Iraq during that era. Keywords: Gulf War, Iraqi Uprisings